2020
DOI: 10.4018/978-1-7998-1093-3.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Oil Prices and Economic Growth in Major Emerging Economies

Abstract: There is a strong correlation between energy prices and economic activity. The relationship particularly holds true for crude oil as changes in oil prices are associated with changes in production costs, and economic activity also generates significant demand for energy and crude oil. This chapter examines the relationship between economic activity and crude oil prices using causality tests in the frequency domain and taking into account the difference between positive and negative changes in both oil prices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, the most recent literature focused more upon the oil prices volatility and economic growth. Such studies include Aloui et al (2018) , Prabheesh and Laila (2020) , Baek et al (2020) , Baek and Young (2020) , Mukhtarov et al (2020) , Katırcıoglu et al (2020) , E.I. Cevik et al (2020) , Cevik et al (2020: pp.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most recent literature focused more upon the oil prices volatility and economic growth. Such studies include Aloui et al (2018) , Prabheesh and Laila (2020) , Baek et al (2020) , Baek and Young (2020) , Mukhtarov et al (2020) , Katırcıoglu et al (2020) , E.I. Cevik et al (2020) , Cevik et al (2020: pp.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative tests such as Granger causality, quantile regression, couple functions, generalised autoregressive conditional heteroskedasticity (GARCH), and vector autoregression have been common to assess the co-movement and test for the effect of oil price change [ 40 , 41 ]. Amongst the different co-movement assessments, the linkage between oil price change and the stock market gained significant attention with the hypothesis that stock market performance reflects a healthy economy [ [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. In the reviewed studies, it was observed that the effect of oil price changes on the stock market varies depending on the methodology, time horizon, and the distinctive economic structure of the assessed country.…”
Section: Literature Reviewmentioning
confidence: 99%